1993
DOI: 10.1007/bf00267824
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial M cells in the rabbit caecal lymphoid patch display distinctive surface characteristics

Abstract: The follicle-associated epithelium (FAE) in the rabbit caecal lymphoid patch is characterized by the presence of membranous (M) cells, which are believed to be functionally equivalent to those present at other sites of gut-associated lymphoid tissue (GALT). Caecal patch M cells display distinctive features compared with those of other GALT sites, despite similar general morphology and expression of the M cell marker vimentin, suggesting marked heterogeneity in the apical surface of M cells at discrete GALT sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
39
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 25 publications
7
39
0
Order By: Relevance
“…The second theory is that M cells are derived directly from undifferentiated cells in the intestinal crypt. In the rabbit ileal Peyer's patch and appendix, a majority of M cells at the periphery of the lymphoid follicle are located adjacent to the intestinal crypt [9,10]. The finding supports the second hypothesis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The second theory is that M cells are derived directly from undifferentiated cells in the intestinal crypt. In the rabbit ileal Peyer's patch and appendix, a majority of M cells at the periphery of the lymphoid follicle are located adjacent to the intestinal crypt [9,10]. The finding supports the second hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…The first hypothesis is that M cells transform from mature microvillous epithelial cells of the FAE [3,[17][18][19]. The second is that M cells differentiate directly from undifferentiated cells in the crypt [4,[8][9][10]. In the rabbit intestine, the cellular kinetics of villous columnar epithelial cells has not yet been clarified, although the morphology and distribution of M cells have been reported in detail [8,10].…”
mentioning
confidence: 99%
“…Previous lectin histochemical studies on the rabbit gutassociated lymphoid tissue demonstrated that M-cells of the rabbit cecal lymphoid patch express high levels of ␣ 1-2-linked fucose and GalNAc residues in their apical membrane (Gebert and Hach 1993;Jepson et al 1993a). Although the biological significance of these membrane-bound glycoconjugates is not completely understood (Clark et al 1993;Gebert and Hach 1993;Jepson et al 1993a;Giannasca et al 1994), the rabbit cecal patch represents an appropriate model for studying the origin, differentiation, and migration of M-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological significance of these membrane-bound glycoconjugates is not completely understood (Clark et al 1993;Gebert and Hach 1993;Jepson et al 1993a;Giannasca et al 1994), the rabbit cecal patch represents an appropriate model for studying the origin, differentiation, and migration of M-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation